Worker-centered investigation of issues with procedural systems: Findings from interviews with a representative sample of workers in high-risk process industries. (September 2020) - Peres, S. Camille; Smith, Alec; Sasangohar, Farzan
Abstract: Issues related to procedural systems have been found to contribute to incidents in many high-risk industries such as petrochemical, oil and gas, etc. While previous research has focused on understanding issues with procedural systems from the perspective of the workers (who are the end-users of procedures), most of this research suffers from samples that only include companies with programs focused on improving safety by improving procedures. These companies may have inherent differences in their safety practices and thus the experiences of these workers may not completely represent all workers' experiences in this domain. The purpose of this study is to gain insights into the thoughts and perceptions from a representative and broad sample of workers concerning procedure use and purpose. To improve the generalizability of previous findings, interviews were conducted with workers from a broad range of high-risk process industries to investigate issues related to procedure adherence that may be present in companies not currently implementing. Findings from a qualitative data analysis provide support for the generalizability of issues previously discovered, such as: more experience workers being more likely to deviate; procedure quality being inconsistent; and the procedure revision process being problematic. However additional prominent issues were found as well. Most importantly, this study found that adherence to procedures is often motivated by potential liability issues instead of genuine concerns for safety in organizations and many deviations from procedures were due to pressure from immediate supervisors. These findings suggest a relationship between the effectiveness/quality of procedural systems and the safety climate of the organization or work unit. Highlights: Research on adherence to procedural systems should use a representative sample. Adherence is motivated by liability issues instead of safety concerns for safety. Many deviations from procedures were due to pressure from supervisors. Effectiveness/quality of procedural systems and safety climate are intertwined.